Aid for Trade : An Action Agenda Looking Forward - Hoekman, Bernard (World Bank, Washington, DC, 2012)
The current post-crisis environment and fragile economic recovery increases the importance of aid for trade. Global rebalancing and tightened fiscal budgets in the short to medium term also place renewed emphasis on aid effectiveness. This note identifies four options to enhance the effectiveness of the multilateral aid for trade initiative: (i) expanding market access for least-developed countries (LDCs) through leadership by middle-income G-20 members; (ii) creating a mechanism to identify good practices in domestic regulation of service markets and other 'behind-the-border' trade-related policies; (iii) leveraging the dynamism and knowledge of the private sector to improve trade facilitation and build capacity; and (iv) but a renewed 'activism' by government in the trade and growth agenda need not mean.